أثَرُ الورّاقين في انتشارِ الخطِّ العربيّ الورّاقون اللغويون أُنموذَجاً - انتصار هندي تبن بدر الدليمي (Universitas Negeri Malang, 2023)
The research deals with an aspect of Arabic calligraphy, the reasons for its spread, and discusses the questions it raises within it and solves its problems; since the relationship of human communication, either spoken or written, speech Calligraphy is written speech, and herein lies its importance as one of the links of communication between nations. It also deals with the paper and its impact on the spread of Arabic calligraphy, its definition, importance, and role in spreading Arab culture. Intellectuals are masters of science, as it is the way to disseminate scientific output, in addition to translation. Because of its great role in revitalizing the Arab mind, it enriched the Arab library with various Greek, Syriac, Indian, Persian, and other sciences and philosophies. He mentioned the tools of calligraphy, its pests, and the conditions that must be met by the linguists and the owners of this craft, after which I shed light on three scholars who worked on the paper, and concluded it with results, after which I mentioned the sources and references from which the research material was drawn. يتناول البحث جانباً من جوانب الخطِّ العربي، وأسباب انتشاره، ويناقش تساؤلات يطرحها في ثناياه وحل إشكاليتها، وبما أنّ صلة التواصل البشري؛ إما كلام منطوق أو مكتوب فالخطّ هو الكلام المكتوب، وهنا تكمن أهميته كونه أحد صِلات التواصل بين الأمم، ويتناول أيضاً الوِراقة وأثرها في انتشار الخط العربي، والتعريف بها وأهميتها ودورها في نشر الثقافة العربيَّة، فقد حظيت هذه الحِرفة منذ عصر مبكر من تاريخ المسلمين باهتمام المؤلفين والمثقفين من أرباب العلم، فهي السبيل لنشر النتاج العلمي، بالإضافة إلى الترجمة؛ لما لها من دور كبير في تنشيط العقل العربي؛ إذ أثْرَتْ المكتبةَ العربيةَ بمختلف العلوم والفلسفات اليونانية والسريانية والهندية والفارسية وغيرها، وذِكر أدوات الخطّ وآفاته والشروط الواجب توافرها في الوراقين، وأصحاب هذه الحِرفة من اللغويين، بعدها ألقيتُ الضوءَ على ثلاثةِ علماءَ عملوا بالوِراقة، وختمته بنتائجَ، ثم أردفتها بتوصيات، بعدها ذكرت المصادر والمراجع التي استقيت منها مادة البحث.